2015
DOI: 10.3390/toxins7103858
|View full text |Cite
|
Sign up to set email alerts
|

Mycobiota and Mycotoxins in Traditional Medicinal Seeds from China

Abstract: The multi-mycotoxin occurrence for internal and superficial fungi contamination were comprehensively assessed in medicinal seeds used as food or beverage. Based on a polyphasic approach using morphological characters, β-tubulin and ITS gene blast, a total of 27 species belonging to 12 genera were identified from surface-sterilized seeds. Chaetomium globosporum was most predominant (23%), followed by Microascus trigonosporus (12%) and Alternaria alternata (9%). With respect to superficial mycobiota, thirty-four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…were reported in grains by Martin et al [21] and Barros et al [22]. Chen et al [17] offered a similar explanation for the prevalence of Fusarium where Aspergillus and Penicillium were not recorded.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…were reported in grains by Martin et al [21] and Barros et al [22]. Chen et al [17] offered a similar explanation for the prevalence of Fusarium where Aspergillus and Penicillium were not recorded.…”
Section: Discussionmentioning
confidence: 67%
“…It has been shown that Fusarium , Phoma , Alternaria , Penicillium , Aspergillus , and Cladosporium spp. are the commonly isolated mycoflora from cereal seeds and other plant seeds [13,17,18,19,20]. Almost all the common species were detected except Penicillium and Aspergillus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [2 ] assessed internal and superficial fungal contamination and multi-mycotoxin occurrence in medicinal seeds used as food in China. The superficial mycobiota on seed surfaces included 34 species (17 genera).…”
Section: Fungal Occurrence In Plant-based Supplements and Medicinesmentioning
confidence: 99%
“…Aflatoxins including AFB1, AFB2, AFG1, and AFG2 are mycotoxins produced by Aspergillus flavus and A. parasiticus, with potent carcinogenic activity, especially on human liver [ 1 ]. Aflatoxins can be accumulated in humans and livestock through diet of aflatoxin-contaminated foods and feed [ 2 , 3 ]. Outbreaks of aflatoxicosis are notably dependent on the crop species and seasonal changes of a given region [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%